Prevalence and Risk Factors of Caprine Gastrointestinal Parasites in and around Rewa, Madhya Pradesh, India - Maravi, Durpat S.; Dixit, Pooja; Dixit, Alok K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Prevalence studies are important for the control of parasitic diseases. A total of 1003 fecal samples of goats in and around Rewa werescreened with standard flotation and sedimentation methods. The overall prevalence of gastrointestinal parasites was 92.52% ingoats. The maximum prevalence of strongyles was 92.22% followed by coccidia (27.22%), Trichuris spp. (13.06%) and Moniezia spp.(7.78%). The prevalence was significantly higher (p
Keywords: Gastrointestinal parasites; Goat; Prevalence; Seasonal changes.